The effect of zinc on anaphylaxis in vivo in the guinea-pig. - Cho, C H (1977)
The protective effects of pretreatment with zinc sulphate aerosols against bronchoconstriction induced by egg albumen or histamine aerosols were assessed in sensitized or non-sensitized guinea-pigs respectively. Pretreatment with an adequate concentration of zinc sulphate aerosol significantly prolonged the time of onset of bronchoconstriction in sensitized guinea-pigs challenged with egg albumen, but did not appreciably alter the onset time of histamine-induced bronchoconstriction in non-sensitized animals. These findings suggest that zinc aerosols may be of prophylactic value against bronchoconstriction of allergic origin.